(untitled) (Fiep Bulletin - online, 2019)
Human development results from interactions between characteristics of the organism and the different contexts andtasks to which the individual is exposed. During the years of early childhood education, children are usually in the phase offundamental movements, where the main changes occur in the way of refinement of motor skills and better efficiency in theircombination (GABBARD, 2000; GAYAHUE, 2002; HAYWOOD, GETCHELL, 1998). The aim of this study is to analyze the motorperformance of children in pre-school education in physical education classes through the observation of teachers and theauthor. Methodology: The research is qualitative, being used interviews to the teachers of the classes of Physical Education andobservation of the author of the aspects: spatial notion, laterality, reaction time and balance in the classes of Physical Educationin children of schools of high social class of the city of Vitoria-ES. Results: The results show that more than half of each class hasdifficulty performing the movements used in Physical Education classes in which the teacher prepares according to the age groupof the class. Conclusion: It is concluded that the students of Physical Education of the upper-class schools have little mastery ofthe body itself. Children with gait difficulty and movements requested in class.